Implementation of E-Court In The Examination of Civil Cases at The Source District Court - Sekar Mutiara; Neni Triana; Aldi Ferdiansyah; Pera Pera; Rifal Feliansyah; Galih Putra Pamungkas (Jurnal Abdisci, 2025)
Abstract: Background. Formal civil law is based on several existing legal foundations. One of them is the principle of judicial trilogy, also known as the principle of easy, fast, and low cost. E-Court is a site for all registered account owners to register cases online and find out about online advances, online payments, calls made through electronic channels, and the implementation of hearings held through electronic media (E-Litigation). Based on the explanation above, the problem to be known is how to apply the E-Court system as an application on the principle of easy, fast, and low cost in the Source District Court. Aims. The study aims to measure the application of the E-Court system in the Source District Court. Methods. The research method used is sociological legal research, which involves collecting primary and secondary materials. Primary data was obtained through interviews with the Sumber District Court officers, namely the Chief Justice, Judge, Chief Registrar, Junior Civil Registrar, and Lawyer at the Posbakum. Then, secondary data was obtained through a literature study, such as the Law, as well as literature books related to an E-Court system, to support this writing. Result. The study's results show that the various features provided in E-Court have fulfilled the principle of easy, fast, and low cost. Conclusion. Implementation. However, in its implementation at the Sumber District Court, problems such as interference with the network and servers in the E-Court system were still found.